Description, and pilot evaluation, of novel staff education to improve care of confused older inpatients - Horner, B.; Watson, N.; Hill, Anne-Marie; Etherton-Beer, C. (2014)
Objective To determine feasibility of novel staff education aiming to optimise care for confused older people. Design Pre/post qualitative study. Setting Tertiary teaching hospital. Subjects Clinical staff in two geriatric medicine wards. Interventions Self-directed learning modules, with access to an education resource officer to reinforce learning in real time. Main outcome measures Primary outcomes were feasibility (proportion of staff completing the education) and perceived effectiveness (measured in focus groups and individual interviews). Results Twenty-six staff agreed to undertake the education; six confirmed completion of the entire learning package. Participants were enthusiastic about education regarding confused older people. Participants who completed the education modules reported they were satisfied with the format and content of the learning materials, but cited time constraints as a major barrier. Conclusion Participants expressed need and enthusiasm for education but uptake of the package was less than anticipated. Organisational support (such as providing staff with protected paid time to complete education) may be required to improve adherence.